Short communication. Sequence of mspl gene of Anaplasma marginale Havana isolate and expreáion in eukaryotic cells - Corona, B.=700 1 Minet, C.; Albina, E.; Vega, A.; Martinez, S.
(Es, En)
ilus., 27 ref.
Keywords: ANAPLASMOSIS; ENFERMEDADES INFECCIOSAS; GANADO BOVINO; ANAPLASMA; RICKETTSIALES; ESPAÑA; MSPL; PRINCIPALES PROTEINAS DE SUPERFICIE